The Influence of Word of Mouth and Sales Promotion on Purchasing Decisions at Xyz Cafe in Medan - Sjukun (PT FORMOSA CENDEKIA GLOBAL, 2023)
Sales promotion is one of the factors that can influence purchasing decisions. Marketing strategies through word of mouth and sales promotions carried out by other similar business actors so that there are more and more business competitors. The data analysis method used in this research is quantitative method. The data collection technique for this research is to use documentation and questionnaires. And the data quality test uses validity test, reliability test, classical assumption test, multiple linear regression, t test, F test, and coefficient of determination. The conclusion that can be drawn from this research is that word of mouth has an effect on purchasing decisions at Cafe XYZ in Medan, then it is known that sales promotion has no effect on purchasing decisions at Cafe XYZ in Medan.